Smart Flow Computer: Leveraging IoT for Accurate and Efficient Gas Flow Measurement in The Oil and Gas Industry - Suka Handaja,; Astrie K. Dewi,; M. Raihan De Lafayatte,; M. Ramdhan, (International Journal of Integrated Engineering, 2025)
Accurate measurement of gas flow is crucial in the oil and gas sector, typically accomplished using orifice sensors and based on AGA report 3 standards. This research obtains a flow computer configuration to meet the increasing need for accurate and efficient remote meter reading, integrating IoT technology for real-time monitoring, and utilizes complicated calculations based on AGA report 3 namely Smart Flow Computer. The study implements and assesses the Smart Flow Computer, which uses an ESP32 microcontroller and a current-to-voltage converter, against the Kelton Flocalc software. The verification of pressure, differential pressure, and temperature outputs revealed relative deviation ranging from 0% to 0.23%. These inaccuracies are attributed to signal impurity, measurement uncertainty, and equipment resolution. The ESP32's 12-bit ADC, which has 4096 levels, has a deviation less than 1%. This contrasts with the 14-bit ADC, with 16,384 levels, found in conventional flow computers. This research shows that the ESP32-based Smart Flow Computer has high accuracy with minimal deviation, meeting the standards set by the metrology directorate, indicating its potential to revolutionize remote gas flow monitoring in the oil and gas industry. By integrating IoT technology and advanced microcontrollers, this innovative solution offers real-time data acquisition and reliable calculations, significantly improving operational efficiency and precision.